Variasi Bahasa Sosiolek pada Movie Detective Conan: Crimson Love Letter - Risma Shelsha Dilha; Ni Wayan Meidariani (AYUMI : Jurnal Budaya, Bahasa dan Sastra, 2025)
Sociolect, a branch of sociolinguistics, examines language variations influenced by social class, community groups, and the status of speakers. One form of sociolect is colloquial language, an informal type of speech commonly used in daily interactions. This study aims to describe the use of colloquial language variations in the anime Detective Conan: Crimson Love Letter, focusing on how such language reflects the social dynamics among characters. The research was conducted using a descriptive qualitative approach based on primary data collected directly from the anime's dialogues. The analysis revealed five colloquial language variations influenced by factors such as situation, age, social status, gender, and geographical background. These findings demonstrate that the use of colloquial language not only enriches character portrayal but also strengthens the emotional connections in their communication. Keywords: anime; colloquial; Detective Conan; movie; Sosiolect